FEATURES OF PHYSICAL DEVELOPMENT AND TOOTH DECAY MORBIDITY IN CHILDREN WHO LIVE IN ENVIRONMENTALLY ADVERSE CONDITIONS - L.S. Lagoda; H.G. Musji-Sementsiv; T.Y Lisak (Український стоматологічний альманах)
Introduction. Physical development of children is one of the important indicators of the health of the children's population. The state of physical development of the child to a certain extent is reflected in the vital activity of the child's body and is the basis for preventing the emergence of a number of pathological disorders.